Pupil dilation responds to the intrinsic social characteristics of affective touch - Greta Bonino; Alessandro Mazza; Francesca Capiotto; Annamaria Berti; Lorenzo Pia; Olga Dal Monte (Scientific Reports)
Abstract Affective Touch is characterized by both emotional and arousing dimensions that rely on specific features of a gentle human caress. In this study, we investigated whether and how both the nature of the touching effector (Human hand vs. Artificial hand) and touch type (Dynamic vs. Static) influenced the participants’ pupil dilation and their subjective experience during tactile stimulation. We observed that when participants received a dynamic touch, their pupil dilation increased more when the touch was produced by a human compared to an artificial hand. This discrimination was not present for static touch. Also, dynamic touch given by a human hand invoked a supralinear enhancement of pupil dilation indicating that the combination of these two features induced a stronger autonomic activation than the summed effects of each separately. Moreover, this specific type of touch was perceived as the most pleasant compared to all other tactile stimulations. Overall, our results suggest that pupil dilation could reflect the pleasant experience of human-to-human tactile interactions, supporting the notion that the autonomic nervous system is responsive to the emotional and hedonic aspects associated with Affective Touch as a part of a complex and holistic social experience, rather than solely reacting to its low-level sensory properties.